Pengembangan Materi Donner des Informations Personnelles Melalui Media Pembelajaran Berbasis Virtual Reality pada Keterampilan Menyimak Bahasa Prancis - Andika, Yunilis; Ekowati, Sri Harini; Ismail, Subur (Universitas Pendidikan Indonesia, 2023)
Efforts to attract students' interest in the learning process need to be carried out by the teacher. In the 21st century, the use of technology is the main key to applying interesting and fun learning media, especially in French listening skills. The difficulty of students in listening to foreign language speech is often encountered because they have insufficient background knowledge to support their hearing. For this reason, the application of technology-based learning media, especially virtual reality in French, can be done. This research is included in the development research design. The development steps according to the Lee and Owens (2004) development model include (1) analysis, (2) design, (3) development, (4) implementation, and (5) evaluation (evaluation). The data collection technique used was in the form of a document study to determine the material to be developed based on the Alter Ego 1+ textbook. The material is analyzed first, then applied to virtual reality-based learning media. The use of this media can be a good strategy to motivate students in listening skills.